The Effect of E-Module on Activity and Learning Outcomes on Electrolyte and Nonelectrolyte Solutions - Damanik, Nova; Riris, Ida Duma; Sitorus, Marham; Sihombing, Junifa Layla; Syafriani, Dewi (Universitas Negeri Medan, 2023)
This research aims to determine activities, learning outcomes and the correlation between activities and student learning outcomes taught using the Project Based Learning (PjBL) learning model assisted by e-modules for class X SMA on electrolyte and non-electrolyte solutions. The population in this study were students of class This research uses test and non-test instruments in the form of student learning activity observation sheets which have been tested and are valid. The data obtained were tested for normality and homogeneity. Based on the results of data processing that has been analyzed, there are learning outcome values tcount = 9.714 and ttable = 1.66, the activity obtained is tcount = 6.069 and ttable = 1.66. Where tcount>ttable shows that Ha is accepted and H0 is rejected, so it can be concluded that there is an influence of the Project Based Learning (PjBL) learning model assisted by e-modules for class X SMA on electrolyte and non-electrolyte solutions. The correlation test was carried out to determine the significant correlation between activities and student learning outcomes. The research results show that rcount > rtable (0.929 > 0.329) so H0 is rejected. Thus, there is a significant correlation between activities and student learning outcomes assisted by e-modules for class X SMA on electrolyte and non-electrolyte solutions.